PENGARUH VARIASI KONSENTRASI EKSTRAK BELIMBING WULUH (Averrhoa bilimbi L.) PADA SEDIAAN GEL TERHADAP STABILITAS FISIK - Sholikhah Deti Andasari; Sutaryono Sutaryono; Isnaini Nur Hartanti (Universitas Muhammadiyah Klaten, 2018)
Abstract: Averrhoa bilimbi L. was used as an anti-acne drug. The content offlavonoid compounds in fruit have antibacterial activity. There were several waysfor utilization of Averrhoa bilimbi L. among others, made some preparations,especially gel formulation. Gel formulations made with HPMC base and add fruitextract 15%, 20%, and 25%. Fruit extract obtained from meserasi fruit Averrhoabilimbi L with 70% ethanol. The gel that has been made is then carried outquality control test such as organoleptic test, pH test, sticky test, spreading test,protection test and physical stability test by stressed condition. Organoleptic testresult, pH test, protection power test, and stability test analyzed descriptively. Theresults of sticky test and scatter power were analyzed with ANOVA with 95%confidence level. The result of this research showed that in the test of spreadingof formula II has good with mean of spreading value was 6,6 before stability testand 6.49 after stability test. In the protection test does not appear red stain. itmean the gel was able to provide protection of the skin.